Identification of a Novel Epigenetic Signature CHFR as a Potential Prognostic Gene Involved in Metastatic Clear Cell Renal Cell Carcinoma - Chen, Xiangling; Lin, Jiatian; Chen, Qiaoling; Liao, Ximian; Wang, Tongyu; Li, Shi; Mao, Longyi; Li, Zesong (Frontiers in Genetics, 2021)
Metastasis is the main cause of treatment failure in ccRCC tumor and the key genes involved in ccRCC metastasis remain largely unknown. We analyzed the ccRCC datasets in The Cancer Genome Atlas database (TCGA) by comparing primary and metastatic ccRCC tumors to search for tumor metastases associated genes, and then carried out analysis of Overall survival, Cox and ROC to obtain potential prognostic markers. Comprehensive bioinformation analysis was performed to identify that the checkpoint with forkhead associated and ring finger domains (CHFR) gene is a reliable candidate oncogene which overexpressed in ccRCC metastatic tumor tissue and the high expression of CHFR indicates poor prognosis. A detailed analysis of the methylation of CHFR in ccRCC tumors showed that three sites within 200bp region of transcription initiation site were significantly associated with prognosis and that hypomethylation was associated with increased CHFR gene expression levels. Knockdown of CHFR in ccRCC cells inhibited cells proliferation, colony formation and migration ability. In summary, our findings suggested that the epigenetic signature CHFR gene is a novel prognostic gene and our findings offered theoretical support for the study of metastasis related genes in ccRCC and provided a new insight for clinical treatment of ccRCC.